Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T23:09:39+02:00
A) 4x + 6 = 6x + 4
4x - 6x = 4 - 6
-2x = -2 /:(-2)
x = 1 - jedno rozwiazanie
b) 4x + 6 = 6x + 2 (6 - x)
4x + 6 = 6x + 12 - 2x
4x - 6x + 2x = 12 - 6
0 = 6 sprzeczność - brak rozwiazan - równanie sprzeczne
c) 4x + 6 = 6x + 2(3 - x)
4x + 6 = 6x + 6 - 2x
4x -6x + 2x = 6 - 6
0 = 0 nieskonczenie wiele rozwiązan - tożsamościowe
1 5 1
2010-04-14T23:10:53+02:00
2010-04-14T23:12:16+02:00
A) 4x+6=6x+4
2x=2
x=1

b) 4x+6=6x+8-2x
4x+6=4x+8

c)4x+6=6x+6-2x
4x+6=4x+6